Improving Community Task Performance through Synchronous Communication in Plastic Waste Management for Rivers - Heni Nuraeni Zaenudin; Hans Van Den Akker (Poltekkes Kemenkes Surabaya, 2025)
The findings of this study can be utilized to enhance the effectiveness of direct communication in outreach programs aimed at reducing plastic waste pollution in rivers. Practically, this research facilitates community understanding, encourages active participation, and promotes better collaboration in efforts to maintain river water quality, particularly in the West Java region. This study used multi-stage sampling to select the areas with the highest pollution levels in West Java Province, Indonesia. From pre-research and observation, two areas were selected, namely Bandung City and Bandung Regency. The area is prone to pollution and flooding due to plastic waste clogging. Respondents were selected as many as 503 heads of families who live about 10 to 100 meters from the river. This research employs the statistical analysis to examine the relationships between variables in plastic waste management programs. This approach facilitates the prediction of the impact of synchronous communication on community participation in maintaining river water quality. The results of the hypothesis test showed that there was a positive and significant relationship between the tested constructs. The synchronous communication construct affects the Communication Process, which in turn influences Communication Performance and Task Performance. The communication process that produces good sharing understanding will increase the involvement and participation of the community to be involved in the task of cleaning up plastic waste in rivers. Community participation since 2008 has had a positive significance with the improvement of river water quality in West Java, Indonesia.